Transcriptome analysis of pika heart tissue reveals mechanisms underlying the adaptation of a keystone species on the roof of the world - Mu, Danping; Wu, Xinlai; Feijó, Anderson; Wu, Wei; Wen, Zhixin; Cheng, Jilong; Xia, Lin; Yang, Qisen; Shan, Wenjuan; Ge, Deyan (Frontiers in Genetics, 2022)
Abstract High-altitude environments pose intense stresses for living organisms, which has driven striking phenotypic and genetic adaptations. For example, hypoxia resistance, cold tolerance, enhanced metabolic capacity and enhanced body masses. As one of the most successful and dominant mammals on the Qinghai-Tibet Plateau (QHTP), the plateau pika (Ochotona curzoniae) has adapted to the extreme environment on the top of this region and exhibits tolerance to cold and hypoxia, which is in contrast to its closely related species that inhabit the peripheral alpine bush or forests. To explore the potential genetic mechanisms underlying the adaptations of O. curzoniae to a high-altitude environment, we sequenced transcriptomes from the heart tissues of the adult plateau pikas and Gansu pika (O. cansus), the former with comparisons from sites of two different altitudes. Differential gene expression analysis (DEG) and weighted correlation network analysis (WGCNA) were conducted to identify differentially expressed genes and their primary functions. The principal component analysis showed a significant differentiation in the expression patterns between the two pika species. Additionally, we detected weak differences between plateau pikas from distinct altitudes. Genes identified in DEG and WGCNA were mainly enriched in signal transduction, energy metabolism, and substance transport. Our results showed that the plateau pika has adapted to the extreme environments of the QHTP by protecting cardiomyocytes, tissue structure of matter, and improving the blood circulation system and energy metabolism. These adaptations shed light on how pikas thrive on the roof of the world.